Analysis of the Effectiveness of Geographic Information Systems for Natural Disaster Data Management in Indonesia - Maesaroh (Yayasan Banu Haji Samsudin, 2025)
This study aims to analyze the effectiveness of Geographic Information Systems (GIS) in managing natural disaster data in Indonesia through a qualitative approach based on literature studies. Indonesia as an archipelagic country located in the Pacific ring of fire region has a high risk of natural disasters such as earthquakes, volcanic eruptions, floods, and landslides. Fast, accurate, and integrated disaster data management is an urgent need in disaster mitigation and management efforts. GIS is considered to be able to present relevant spatial and temporal information to support decision-making by policymakers and emergency response agencies. This study examines various scientific literature, policy reports, and official documents from 2015 to 2024 to evaluate the contribution of GIS in the context of disaster management in Indonesia. The results of the study show that GIS is effective in mapping disaster-prone areas, supporting early warning systems, and improving coordination between agencies through map-based visual data. However, challenges are still found in terms of data integration between regions, limited human resource capacity, and lack of standardization of spatial data. Therefore, strengthening technical capacity and developing policies based on spatial data needs to be improved. This research is expected to make a theoretical and practical contribution to the development of a sustainable and adaptive geographic information system to disaster dynamics in Indonesia.